Role of physical activity in bone health in peripubertal boys. Issue 5 (17th June 2014) - Ivuškāns, Arturs; Jürimäe, Toivo; Lätt, Evelin; Jürimäe, Jaak; Purge, Priit; Saar, Meeli; Maasalu, Katre; Mäestu, Jarek
Abstract Background The aim of the present cross‐sectional study was to investigate the relationship of physical activity level to bone mineral parameters in 11–13‐year‐old boys. Methods In total, 264 boys, divided into normal weight (n = 154) and overweight (n = 110), participated in this study. Physical activity was measured via 7 day accelerometry and bone mineral parameters using dual‐energy X‐ray absorptiometry. Results In overweight boys, vigorous physical activity was associated with total bone mineral density (BMD), total bone mineral content (BMC), while moderate–vigorous physical activity MVPA was associated with femoral neck BMD. In normal weight boys, however, only vigorous physical activity was associated with femoral neck BMD. When the normal weight group was divided into tertiles according to MVPA, femoral neck BMD was higher in the highest tertile compared to the lowest tertile. No other significant differences were found in bone mineral parameters according to the tertiles of MVPA. Conclusions In overweight peripubertal boys, physical activity is more associated with bone mineral parameters compared to normal weight subjects. In addition to vigorous physical activity, moderate physical activity has a significant impact on bone mineral parameters in overweight subjects.